FOOD PRODUCTS AIMED AT IMPROVING THE HEALTH STATUS OF CHILDREN AND ADOLESCENTS, AND THE HYGIENIC SUBSTANTIATION AND IMPROVEMENT OF DIETARY NUTRITION (Eureka Journal of Health Sciences & Medical Innovation, 2026)
This article examines the hygienic substantiation and improvement of food products intended to enhance the health status of children and adolescents within the framework of modern preventive medicine and nutrition hygiene. The health of the younger generation is closely associated with the quality, safety, nutritional value, and physiological adequacy of daily nutrition. In conditions of rapid urbanization, changing dietary habits, reduced physical activity, and increasing consumption of highly processed foods, the development of scientifically grounded dietary products has become one of the urgent directions of public health. The paper considers the role of specialized food products enriched with essential nutrients, vitamins, minerals, probiotics, prebiotics, and biologically active components in supporting normal growth, development, immunity, cognitive performance, and disease prevention among children and adolescents. Particular attention is given to hygienic principles in the formulation, evaluation, and practical implementation of dietary nutrition, including age-specific physiological needs, sanitary safety, digestibility, balanced composition, and risk reduction for nutrition-related disorders. The article also highlights the significance of school nutrition systems, functional foods, and preventive dietary strategies in reducing micronutrient deficiencies, obesity, gastrointestinal disturbances, and metabolic imbalance. It is argued that the improvement of dietary products for children and adolescents should be based on interdisciplinary cooperation among hygienists, pediatricians, nutritionists, technologists, and public health specialists. Scientifically substantiated and hygienically optimized nutrition contributes not only to the prevention of disease, but also to the formation of a healthier and more resilient younger population.
Keywords: Children’s health, adolescent nutrition, dietary nutrition, hygiene of nutrition, functional food products, preventive nutrition, balanced diet, micronutrient deficiency, healthy food products, sanitary safety